The n_ToF facility for Nuclear Astrophysics - Cosentino Luigi; Massimi Cristian (EPJ Web of Conferences)
Neutron-induced reactions involved in cosmological and stellar nucleosynthesis processes, represent key inputs for astrophysical models of the chemical evolution of the universe. Accurate knowledge of cross sections is essential to ensure high reliability of these models and to address discrepancies that still exist between models and observations. The availability of neutron beams with both high flux and energy resolution, combined with a large variety of innovative detectors, makes the n_TOF facility at CERN a unique tool for performing accurate measurements of astrophysical interest, even for challenging reactions involving very short-lived isotopes. In more than 20 years, about 70 experiments of astrophysical interest were successfully performed, including 10 measurements with radioactive isotopes. The recent successfully measurements of a 204Tl sample with mass a few mg and 100GBq of γ-activity, confirmed the great potential of the facility in tackling increasingly challenging measurements. Furthermore, the ongoing development of the NEAR irradiation area, where a 108 n/s neutron beam with a Maxwellian energy spectrum will be available, is expected to open new experimental scenarios. This will shed light on unresolved questions in nuclear astrophysics, such as those related to exotic processes like the intermediate nucleosynthesis (i-process).